Kedudukan Wanita dalam Ranah Politik di Indonesia Menurut Pandangan Islam - Andi Candra Jaya (An Nisa'a, 2018)
The important role of Indonesian women in the political activities has stretched in the long period. Indonesia's constitution and legislation also guarantees the active role of Indonesian women in the political activities by limiting at least 30% of women's involvement in political party stewardship, political position candidates to the quota of 30% of women in DPR, DPD and DPRD. As a predominantly Muslim country and the involvement of Muslim women who are quite active in the political activities, it is important to know how Islam views the position of Indonesian women in the political activities. Knowing this, Indonesian women, especially Muslims, can have clear religious legitimacy for their political movements and struggles. By library research method data collected and then analyzed by comparative method then presented in comparative descriptive discussion, with step: first, raised how woman position in Indonesia in political sphere. Second, it raises how the Islamic view of women's position in the political sphere. Third, using the Islamic view to highlight the position of women in the political activities in Indonesia. In the context of today's modern civilization, democracy through its instruments of executive and legislative institutions is a formal legal means for citizens to channel their aspirations, fight for their rights and uphold justice and truth through the formulation of public policy. The involvement of women in the political activities is very important because only by their involvement, their aspirations, needs and interests can be identified, channeled and formulated into public policy. This struggle is not at all contrary to the rules of Islam. Islam actually obliges its adherents to always fight for justice, uphold the truth and defend the rights of the weak dan the have not people. Islam calls it an obligation to help each other in goodness, justice and truth. What is forbidden by Islam is helping each other in sinful acts. During the context of helping each other in goodness, justice and truth then it is precisely an obligation that must be fought either by muslim, man or women.